1996
DOI: 10.1051/parasite/1996033229
|View full text |Cite
|
Sign up to set email alerts
|

Human cutaneous leishmaniasis: ultrastructural interactions between the inflammatory cells and leishman bodies in the skin lesions

Abstract: Summary :The ultrastructural interactions between the inflammatory infiltrate and Leishman bodies (LBs) were described in skin lesions from 16 patients with acute cutaneous leishmaniasis. In early stages of the inflammation, the cellular infiltrate consisted of both undifferentiated and differentiated (activated) monocytes (M), macrophages (Mc), multinucleated giant cells (MNGC), plasma cells (PC), lymphocytes (Ly), and fibroblasts (F). In late stages, the infiltrate was in the form of tuberculous granulomas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The infiltrate is composed predominantly of macrophages with a mixture of lymphocytes and multinucleated giant cells. Plasma cells may be found in variable amounts and may contain eosinophilic ‘Russel bodies' indicating immunoglobulin production [7]. Neutrophils and eosinophils are present in variable amounts but are usually few in number.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…The infiltrate is composed predominantly of macrophages with a mixture of lymphocytes and multinucleated giant cells. Plasma cells may be found in variable amounts and may contain eosinophilic ‘Russel bodies' indicating immunoglobulin production [7]. Neutrophils and eosinophils are present in variable amounts but are usually few in number.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…The most studied non-canonical Leishmania host cells are fibroblasts [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. They can migrate within the skin tissue [ 8 ], potentially allowing Leishmania to spread from the site of transmission, thereby disseminating the infection and enhancing the possibility of being engulfed by the vector during blood feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have reported that fibroblasts harbour Leishmania amastigotes ( Table 1 ) [ 8 , 9 , 10 , 11 , 14 , 81 , 83 , 84 , 85 , 86 , 87 ]. Conflicting results have been observed regarding the survival of L. amazonensis in fibroblasts, ranging from limited survival of parasites (e.g., [ 12 , 91 ]) to their successful multiplication [ 8 , 10 , 14 , 15 ] ( Table 1 ).…”
Section: Other Potential Host Cells Of Leishmaniamentioning
confidence: 99%